Determination of Antioxidant Compounds, Antibacterial Activity and Minerals Content of Broccoli - Dhuha M.A.AL-Altaie; Zuhair Radhi Addai (Institute of Medico-legal Publications Pvt Ltd, 2021)
The aim of this study was to examine the antioxidant compounds, antibacterial activity and minerals content of broccoli stem and floret. The antioxidant activity was determined by measuring total phenolic content (TPC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH). The antibacterial activity was determined using paper disc method against two bacteria namely Klebsiella sp, Escherichia coli, Staphylococcus aureus and P. aeruginosa. Minerals concentrations of broccoli stem and floret were determined using atomic absorption spectrometry. The results showed that floret sample had significantly (P <0.05) higher total phenol content and antioxidant activity compared to stem sample. The result showed that the acetone extracts of broccoli stem and floret were effective against all the bacteria tested. The majority of the broccoli materials were rich in some of the essential minerals like Na, K, Ca, Mg, Mn, Cu, Fe, and Zn, which are known to be beneficial for health. In general, the concentrations of minerals in the broccoli stem and floret were detected. broccoli floret higher minerals concentration of K, Ca, Mg, Mn, Cu, Fe, and Zn of floret than stem. Results showed part of plant effect of the antioxidant compounds and minerals content. Results of the present study provide vital data on the availability of some antioxidant compounds and essential minerals, which can be useful to provide dietary information for designing value-added foods and for food bio fortification.